2020
DOI: 10.1002/adbi.202000069
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Biological Insights from Proteomic Analyses of Extracellular Vesicle Cargos in Normalcy and Disease

Abstract: 2000069 (5 of 16) reports [130,131] of noticeable reduction in high-abundance proteins from biofluids using ultrafiltration, making this approach very attractive for downstream MS applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 205 publications
(357 reference statements)
0
11
0
Order By: Relevance
“…For instance, another important application of EVs proteomic profiling is the identification of disease-associated diagnostic and prognostic markers, as EVs proteome is both cell and disease-type dependent. Indeed, EVs are also capable of shaping the microenvironment as active players also in pathological events, such as metastatic promotion and tumor growth promotion [ 66 , 67 ]. The active involvement of EVs in cancer homeostasis and the fact that their composition reflects the contents of cell of origin make them optimal candidates for biomarker profiling studies.…”
Section: Extracellular Vesicle As Resourceful Biological Systemsmentioning
confidence: 99%
“…For instance, another important application of EVs proteomic profiling is the identification of disease-associated diagnostic and prognostic markers, as EVs proteome is both cell and disease-type dependent. Indeed, EVs are also capable of shaping the microenvironment as active players also in pathological events, such as metastatic promotion and tumor growth promotion [ 66 , 67 ]. The active involvement of EVs in cancer homeostasis and the fact that their composition reflects the contents of cell of origin make them optimal candidates for biomarker profiling studies.…”
Section: Extracellular Vesicle As Resourceful Biological Systemsmentioning
confidence: 99%
“…Several groups reported multi-omic analysis of MPs, thereby analyzing the protein and lipid content of MPs ( 77 80 ). Kowal and colleagues showed that proteomic analysis of MPs using mass spectrometry led to the identification of proteins defining certain subtypes of vesicles ( 77 ).…”
Section: Experimental Techniques To Isolate Quantify and Characterize...mentioning
confidence: 99%
“…Another important application of EVs proteomic profiling is the identification of disease-associated diagnostic and prognostic markers, as EVs proteome is both cell and disease-type dependent. Indeed, EVs are also capable of shaping the microenvironment as active players also in pathological events, such as metastatic promotion and tumor growth promotion [57,58]. The active involvement of EVs in cancer homeostasis and the fact that their composition reflects the contents of cell of origin make them optimal candidates for biomarker profiling studies.…”
Section: Proteomicsmentioning
confidence: 99%